Design and Realization of a Hyperchaotic Memristive System for Communication System on FPGA - Sahin, Muhammet Emin; Guler, Hasan; Hamamci, Serdar Ethem (Int Information & Engineering Technology Assoc, 2020)
In this study, a memristor based hyperchaotic circuit is presented and implemented for communication systems on FPGA platform. Four dimensional hyperchaotic system, which contains active flux controlled memristor is designed by using a smooth continuous nonlinearity. Dynamical characteristics of designed hyperchaotic circuit are examined such as equilibrium points, chaotic attractors, Lyapunov exponents and bifurcation diagram. Furthermore, an electronic circuit model of hyperchaotic system has been modeled and results are submitted. Chaotic circuits are used in communication systems especially in secure communication due to their sensitive dependence on the initial conditions, not periodic, and having a spread spectrum. By using nonlinearity of memristor, the signals obtained from memristor based hyperchaotic system have been realized to analog and digital communication schemes on FPGA platform, which is suitable for re-programmable and reconfigurable systems. The success of memristor based hyperchaotic circuit with FPGA based communication is demonstrated by both simulation and experimental results.
Keywords: chaos; circuit implementation; communication systems; FPGA; memristor; optimization